Comparison of selected gene expression profiles in sensitive and resistant cancer cells treated with doxorubicin and Selol - Dudkiewicz-Wilczyńska, Jadwiga; Grabowska, Agnieszka; Książek, Iza; Sitarz, Karolina; Suchocki, Piotr; Anuszewska, Elżbieta (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study: Cellular resistance is strongly correlated with the risk of failure in doxorubicin (DOX) treatment, and the knowledge of the mechanisms of resistance and its possible modulation is still very limited. Material and methods : In this study, we assessed the effect of 5% Selol and DOX on the expression of genes that affect cell proliferation in the resistant KB-V1 and sensitive HeLa cell lines, using RT2 ProfilerTM PCR Array matrix “Human Cancer Drug Resistance and Metabolism” (SABiosciences). Results : We showed that HeLa and KB-V1 cell lines, characterised by varying susceptibility to DOX, have different genetic profiles as regards the studied genes. KB-V1 cells show overexpression of MYC and BCL2 genes, which encode proteins with anti apoptotic properties. Selol, when used in KB-V1 cells, reduced the expression of MYC and BCL2 genes, suggested as a new therapeutic target in the treatment of cancers resistant to cytostatic drugs.